Identification and characterization of plant materials used by the Malay midwifery in Kelantan - Othman, Rashidi (s.n, 2012)
Traditional Malay midwifery practices exhibit a wide variation in plant materials selection. This study established that plant materials composition selection differs greatly with respect to stage of Malay midwifery practices, environment factor and culture.